ANALYSIS OF IMPROVING ENGLISH SPEAKING SKILLS THROUGH HIGH SCHOOL STUDENTS' TIKTOK CONTENT - Annisa Nur Kholijah; Bunga Malika Putri; Aidil Syah Putra (Media Inovasi Pendidikan dan Publikasi, 2024)
This study explores the use of TikTok to enhance English speaking skills among high school students. TikTok's interactive platform offers opportunities for practicing pronunciation, acquiring vocabulary, and building confidence in speaking English. A literature review method was employed to analyze existing research, highlighting TikTok's effectiveness in language learning despite challenges such as content quality and screen time management. Best practices include curated content selection and promoting digital citizenship. Case studies demonstrate positive outcomes in student engagement and language proficiency. The findings underscore TikTok's potential as a supplementary tool in modern language education, aligning with communicative language teaching principles. Further research should investigate long-term impacts and comparative effectiveness to refine educational strategies.